GROUND COMPLEX DETERMINATION OF THE FLIGHT TRAJECTORY OF A LOW-LYING OBJECT - Kozyuk, A. Y.; Kozlov, A. P. (Electronics and Control Systems, 2018)
Designing a system of protection of the state border on the basis of a capacitive converter. The analysis of the main stages of the system's operation is carried out, its principle of operation. The mathematical model of the system model and algorithm of work is developed. Other systems of territory protection with the further conclusion are considered and investigated. The scheme of the system of protection of the territory of special purpose on the basis of a capacitive converter is considered. It has been established that the designed system of protection of the state border on the basis of a capacitive converter has advantages over existing security systems, which gives it an urgency and impetus for the prospects for further development.